EFFECT OF NPK AND ORGANIC FERTILIZERS ON YIELD AND SEED OIL CONTENT OF RAPESEED (Brassica napus L.) - S., Shilan H.; Hama, Shara J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted at two different research fields (Kanipanka and Qlyasan), at the Kurdistan region of Iraq during winter season (2019- 2020) to investigate the effects of NPK and organic fertilizer application on seed yield and its components, protein, oil content, oil yield, and some fatty acid compositions. The experimental design was a complete block design with three replications. The application of (0.00, 40, 80, and 120 kg NPK ha-1) are the main plots. While three applications of (0.00, 600, 1200 kg organic fertilizer ha-1) for subplots. The 120 kg NPK ha-1 had highest seed and oil yield of 2474.178, and 793.249 kg ha-1, respectively, the average of both locations. The application of 1200 kg organic fertilizer ha-1 gave the maximum seed yield, the oil yield of 2172.642, and 719.463 kg ha-1, respectively, for the average of both locations. Results showed the significant effect of NPK and organic fertilizer applications on the percentage of oleic, linoleic, and stearic acids. The study was proved the significant and highest oil yield when NPK application rate increased from 40 to 120 kg ha-1 and from 600 to 1200 kg organic fertilizer ha-1.